Reactions to using other nicotine and tobacco products instead of menthol cigarettes: A qualitative study of people who smoke menthol cigarettes in the United States - Rachel L. Denlinger-Apte; Ashley E. Strahley; Darcy E. Lockhart; Kimberly D. Wiseman; Rachel N. Cassidy; Danielle R. Davis; Richard J. O'Connor; Jennifer W. Tidey (Preventive Medicine Reports, 2023)
The US Food and Drug Administration is considering banning menthol cigarettes, which could result in some people who smoke menthol cigarettes switching to other tobacco products (OTPs). This qualitative study explored reactions to using OTPs instead of menthol cigarettes. People who smoke menthol cigarettes (N=40) completed a behavioral economic assessment of the effects of menthol cigarette price increases on OTP purchasing. At the highest price, most participants could not afford menthol cigarettes. Instead, they could purchase non-menthol cigarettes, little cigars/cigarillos (LCCs), e-cigarettes, smokeless tobacco, or medicinal nicotine, or they could abstain from tobacco use. Participants used the OTPs they purchased for three days. During follow-up sessions, participants (n=35) completed semi-structured interviews discussing their purchasing-decisions and experiences using OTPs instead of menthol cigarettes. Interviews were analyzed using reflexive thematic analysis methods. Factors influencing purchasing decisions included flavor, price, prior use of OTPs, interest in trying new OTPs, and perceived ability to satisfy nicotine cravings. Participants described positive experiences using e-cigarettes including the “refreshing” menthol flavor, ability to use in places where cigarettes are prohibited, and convenience of use relative to smoking. Among those using non-menthol cigarettes, many reported they were acceptable but less satisfying products compared to menthol cigarettes while others reported negative reactions to them such as tasting like “cardboard”. Reactions to smoking LCCs were mostly unfavorable but participants said it gave them “something to light”. Multiple considerations may affect switching to OTPs in light of pending menthol cigarette regulation including the availability of menthol-flavored alternatives and (dis)satisfaction with OTPs.